Three dimensional multipod superstructures based on Cu(OH)2 as a highly efficient nanozyme. Issue 27 (27th June 2016) - Cai, Ren; Yang, Dan; Chen, Xigao; Huang, Yun; Lyu, Yifan; He, Jinglin; Shi, Muling; Teng, I-Ting; Wan, Shuo; Hou, Weijia; Tan, Weihong
Abstract : A highly efficient nanozyme system, termed a hollow multipod Cu(OH)2 superstructure (HMPS), has been developed via direct conversion from irregular nanoparticles. Abstract : A highly efficient nanozyme system, termed hollow multipod Cu(OH)2 superstructure (HMPS), has been developed via direct conversion from irregular nanoparticles. The HMPS displayed a body size around 150 nm and branch lengths in the range of 150–250 nm. Based on the excellent catalytic properties of HMPS, we developed a simple and highly sensitive colorimetric assay to detect urine glucose, and the results are in good agreement with hospital examination reports.